The 1st International Online Conference on Infrastructures 2022
DOI: 10.3390/engproc2022017025
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Use of Reclaimed Asphalt in Italy towards a Circular Economy: A Top-Down Approach

Abstract: This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https:// creativecommons.org/licenses/by/ 4.0/).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…It is made of natural aggregates covered by a bituminous layer [16], and nowadays, it can be successfully recycled to create new asphalt. Scientific studies [17,18] and some UE countries' experiences [19] have shown the feasibility of incorporating 50-60% or more RAP for new asphalt production [20,21]. However, since road maintenance interventions occur more frequently than new road construction and complete recycling is not permitted, there is a surplus of RAP in developed countries, creating great amounts of readily available material that can potentially be reused [18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is made of natural aggregates covered by a bituminous layer [16], and nowadays, it can be successfully recycled to create new asphalt. Scientific studies [17,18] and some UE countries' experiences [19] have shown the feasibility of incorporating 50-60% or more RAP for new asphalt production [20,21]. However, since road maintenance interventions occur more frequently than new road construction and complete recycling is not permitted, there is a surplus of RAP in developed countries, creating great amounts of readily available material that can potentially be reused [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, since road maintenance interventions occur more frequently than new road construction and complete recycling is not permitted, there is a surplus of RAP in developed countries, creating great amounts of readily available material that can potentially be reused [18]. This is important in Italy, which has the second-highest quantity of available RAP in the EU (9.5 Mt) [21], yet only 20% of that material is reused [19] due to regulatory limits, which, depending on the bitumen type, allow only a maximum of 30%, 25%, and 15% of RAP to be used in bases, base-binders and binders, and wear courses, respectively [22][23][24]. Finding another way to employ RAP can help valorize valuable waste that otherwise will be lost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation